Case Report: Advantages of High-Resolution MRI in Evaluating the Efficacy of Drug Therapy for Intracranial Atherosclerotic Plaques - Zheng, Tao; Liu, Lei; Li, Li; Gao, Yang; Guo, Runcai; Zhou, Zhi; Liu, Zunjing; Liu, Kunpeng (Frontiers in Aging Neuroscience, 2022)
Intracranial atherosclerotic stenosis(ICAS) is one of the main causes of ischemic stroke and transient ischemic attack(TIA). High-resolution magnetic resonance imaging (HR-MRI) allows us to directly observe the intracranial artery wall, accurately assess the condition of the vascular wall, and quantitatively and qualitatively analyze the intracranial atherosclerotic plaque load and plaque composition. We report a case of a woman with severe stenosis of the left middle cerebral artery(MCA) who was found to have almost complete reversal of intracranial atherosclerotic plaques on HR-MRI after 24 months of follow-up, which is very rare in clinical experience.